LINGUIST List Resources for Finnish, Tornedalen - Damir Cavar, eLinguistics Foundation Board Member; Malgorzata E. Cavar, Director of Linguist List (The LINGUIST List (www.linguistlist.org), 2022)
A page listing all resources on The LINGUIST List website which are relevant to this language or language family.